2019
DOI: 10.1155/2019/1970818
|View full text |Cite
|
Sign up to set email alerts
|

CIAPIN1 Targeted NHE1 and ERK1/2 to Suppress NSCLC Cells’ Metastasis and Predicted Good Prognosis in NSCLC Patients Receiving Pulmonectomy

Abstract: Objective. Cytokine-induced apoptosis inhibitor 1 (CIAPIN1) acts as a downstream effector of the receptor tyrosine kinase-Ras signaling pathway and has been reported as a candidate tumor suppressor gene in various cancers. Our current study was aimed at investigating the prognostic impact of CIAPIN1 on Non-Small-Cell Lung Carcinoma (NSCLC) patients and the effect of CIAPIN1 on NSCLC A549 cells’ metastasis. Methods. Western blot analysis was applied to detect CIAPIN1 expression; Kaplan-Meier survival analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…In our research, TEER calculated values were confirmed whether the Caco-2 confluent Transwell® monolayer culture was suitable for the permeation experiments [ 25 ]. The values increased while the culture time was extended, and it reached over 500 Ω ·cm 2 after the incubation, and the data is shown in Figure 4(b) .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In our research, TEER calculated values were confirmed whether the Caco-2 confluent Transwell® monolayer culture was suitable for the permeation experiments [ 25 ]. The values increased while the culture time was extended, and it reached over 500 Ω ·cm 2 after the incubation, and the data is shown in Figure 4(b) .…”
Section: Resultssupporting
confidence: 61%
“…Oxidative Medicine and Cellular Longevity was suitable for the permeation experiments [25]. The values increased while the culture time was extended, and it reached over 500 Ω•cm 2 after the incubation, and the data is shown in Figure 4(b).…”
mentioning
confidence: 94%
“…Lung cancer is the most common cause of cancer-related mortality in the world and composed of small-cell lung cancer and non-small-cell lung cancer (NSCLC) [1]. NSCLC accounts for more than 80% of the diagnosed lung cancer [2,3]. Although improved methods of detection and management of…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of albumin-to-fibrinogen has been used as a biomarker to judge the clinical prognosis of patients with NSCLS ( 25 ). Studies have reported that the ERK1 signaling pathway plays a key role in promoting the proliferation of NSCLC mesenchymal stem cells ( 26 , 27 ). As such, blocking the ERK signaling pathway improves the therapeutic response of patients with NSCLC to EGFR inhibitors ( 28 ).…”
Section: Discussionmentioning
confidence: 99%